2001
DOI: 10.1002/1615-9861(200111)1:11<1415::aid-prot1415>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Oncoprotein 18 levels and phosphorylation mediate megakaryocyte polyploidization in human erythroleukemia cells

Abstract: Megakaryocytes undergo an unusual cell cycle during differentiation that results in polyploidy through largely unknown mechanism(s). It has been shown that serine phosphorylation of oncoprotein 18 (Op18) is required for cell cycle progression specifically at the G2/M transition. Moreover, mutant forms of Op18 that are defective in one or more of the four serine residues induce G2/M arrest and subsequent polyploidization. Op18 phosphorylation is rapidly induced with phorbol myristate acetate (PMA) treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Studies of the expression of stress shock proteins and their functional regulation are an important field in cell biology . Protein expression during heat shock of Jurkat cells has been well characterized. We already found that patterns of extraction proteins from heat-shock were differ from those from nontreated Jurkat cells. , In this time, the relation of heat-shock stress to Jurkat cells and apoptosis induction was investigated using the connected type of microdevice (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the expression of stress shock proteins and their functional regulation are an important field in cell biology . Protein expression during heat shock of Jurkat cells has been well characterized. We already found that patterns of extraction proteins from heat-shock were differ from those from nontreated Jurkat cells. , In this time, the relation of heat-shock stress to Jurkat cells and apoptosis induction was investigated using the connected type of microdevice (Figure B).…”
Section: Resultsmentioning
confidence: 99%